1990
DOI: 10.1177/004051759006000802
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mercerization and Crosslinking of Cotton Fabrics on Dyeing Kinetics of Direct Dyes from Finite Baths

Abstract: Dyeing of cotton fabrics treated with dimethyloldihydroxyethyleneurea and triethanolamine is discussed. Adsorption time curves from finite baths of untreated, mercerized, and crosslinked cotton print cloths have been studied. Mercerization did not change heterogeneous diffusion resistance but increased adsorption equilibrium constants, dyeing affinities, and diffusion coefficients. Maximum dyeing capacities of mercerized cotton were lower. Crosslinking reduced most of the kinetic constants (rate constants, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
2

Year Published

2005
2005
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 7 publications
1
33
2
Order By: Relevance
“…From those results of linear relationships, we believe that the use of the diffusion kinetic equation reported by Chrastil et al 7,8 to study the equilibrium absorption (a e ), rate constant (k'), and structural diffusion resistance constant (n, the index of the pore structure) of the various treated cotton fabrics is suitable. Several data obtained from the dyeing kinetics of eq.…”
Section: Pore Structuresmentioning
confidence: 95%
“…From those results of linear relationships, we believe that the use of the diffusion kinetic equation reported by Chrastil et al 7,8 to study the equilibrium absorption (a e ), rate constant (k'), and structural diffusion resistance constant (n, the index of the pore structure) of the various treated cotton fabrics is suitable. Several data obtained from the dyeing kinetics of eq.…”
Section: Pore Structuresmentioning
confidence: 95%
“…Those figures reveal the linear relationships between the logarithmic values of the dye (direct red 81) absorption (log a) under the different temperatures and the logarithmic val-TRJ TRJ ues of the time intervals of dyeing (log t) over the initial dyeing time duration. From these linear relationships, we concluded that the use of the diffusion kinetic equation reported by Chrastil et al [8,9] to study the equilibrium absorption (a e ), rate constant (k′), and structural diffusion resistance constant (n, the index of the pore structure) of the various treated cotton fabrics was acceptable. Figure 3(a)-(c), respectively, show similar linear relationships for the rates of dye absorption of the cotton crosslinked with DMDHEU alone, DMDHEU-aspartic acid, and DMDHEU-glutamic acid, which were obtained from the samples dyed with direct red 80 at different temperatures.…”
Section: Methodsmentioning
confidence: 90%
“…The higher dye absorption values for the DMDHEU-alpha amino acids were likely to be caused by the different pore structures of the crosslinked fabrics. It is well known that the crosslinking reaction between alpha-amino acid and cellulose is significantly lower than that between DMDHEU and cellulose; however, the reaction between the amino group of amino acids and the Nmethylol group of DMDHEU was significantly higher than that between the N-methylol groups of DMDHEU [9,13]. The degree of condensation reaction between DMDHEU and alpha-amino acid must be different from that of self condensation of DMDHEU, and the pore structure of the treated fabrics would be different from each other.…”
Section: Methodsmentioning
confidence: 93%
“…Direct Red 81 with a molecular weight of 676 g/mol was used to study the pore structures of the steeped-procedure-treated fabrics. We studied the pore structure by using the following diffusion equation: 6,7 a ϭ a e ͓1 Ϫ exp͑ Ϫ kC 0 t͔͒ n ϭ a e ͓1 Ϫ exp͑ Ϫ kЈt͔͒ n (1) where a is the absorption of the dye on cotton in time t, a e is the equilibrium absorption at t 3 ϱ, k is the specific rate constant, kЈ is the rate constant, C 0 is the concentration of cotton in a finite bath, and n is the structural diffusion resistance constant. The higher n is, the larger the pore size is of the treated fabric.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of the linear relationships, we believe that the use of the diffusion kinetic equation reported by Chrastil and coworkers. 6,7 to study the equilibrium absorption, rate constant, and structural diffusion resistance constant (the index of the pore structure) of the various treated cotton fabrics is suitable. Several data obtained from the dyeing kinetics of eq.…”
mentioning
confidence: 99%